Nut Shells as Adsorbents of Pollutants: Research and Perspectives - Papadaki, Maria I.; Mendoza-Castillo, Didilia Ileana; Reynel-Avila, Hilda Elizabeth; Bonilla-Petriciolet, Adrian; Georgopoulos, Stavros (Frontiers in Chemical Engineering, 2021)
Shells, kernels and other wastes have been investigated by researchers as potential adsorbents for a number of pollutants like methylene blue (MB), Remazol Rot RB, acid blue 80, acid blue 324 or as raw materials for the production of activated carbons and bio-chars to serve the same objective. Activated carbons formed by such wastes have been found to remove different heavy metals like uranium, arsenic, and cadmium while their bio-chars removed others like lead and copper. Furthermore, the production of these adsorbents can be combined with additional ways of valorization of this type of wastes like bio-oil or bio-gas generation or even added-value materials extraction. In this work, conducted research on the capacity of pistachio, pecan, cashew nuts and castor seed shells to remove pollutants from synthetic wastewaters is being shown. This type of research needs to be expanded in order to incorporate competitive adsorption, adsorbents regeneration and recovery of adsorbates and performance with real wastewaters, before they find their way to large scale applications for the removal of the respective compounds from natural waters and wastewaters. An appropriate life cycle assessment is also necessary for the evaluation of the environmental benefits arising from their use.